Analysis of N—H...O hydrogen bonds in new C(O)—NH—P(O)‐based phosphoric triamides and analogous structures deposited in the Cambridge Structural Database. (24th March 2013) - Pourayoubi, Mehrdad; Toghraee, Maryam; Divjakovic, Vladimir; van der Lee, Arie; Mancilla Percino, Teresa; Leyva Ramírez, Marco A.; Saneei, Anahid
<x xml:space="preserve">Abstract</x> Five new compounds belonging to the phosphoric triamide family have been synthesized: two of them with the formula XC(O)NHP(O)Y [X = CF3 (1) and CClF2 (2), Y = NHCH2C(CH3)2CH2NH] involving a 1, 3‐diazaphosphorinane ring part, and three 2, 6‐Cl2C6H3C(O)NHP(O)Z2 phosphoric triamides [Z = NHC(CH3)3 (3), N(CH3)(C6H11) (4) and N(CH3)(CH2C6H5) (5)]. The characterization was performed by 31P{1H}, 1H, 13C NMR, IR spectroscopy besides 19F NMR for fluorine containing compounds (1) and (2), and X‐ray single‐crystal structure analysis for (1), (3), (4) and (5). In each molecule the P atom has a distorted tetrahedral environment. The N atoms bonded to P atom have mainly sp2 character with a very slight tendency to a pyramidal coordination for some amido groups. Different types of N—H...O hydrogen bonds have been analyzed for (1), (3), (4) and (5) and 118 other structures (including 194 hydrogen bonds) deposited in the Cambridge Structural Database, containing either C(O)—NH—P(O)[N(C)(C)]2 or C(O)—NH—P(O)[NH(C)]2. The participation of NCP—H...O=P [NCP = the nitrogen atom of the C(O)—NH—P(O) fragment], N—H...O=P, N—H...O=C and NCP—H...O=C hydrogen bonds in different hydrogen‐bonded motifs are discussed. Moreover, the involvement of the O atoms of C=O or P=O in the [NCP—H][N—H]...O=P, [N—H]2...O=P, [N—H]2...O=C and [N—H]3...O=C groups are considered. A histogram of N...O distances, the distribution of N—H...O angles and the scatterplot of N—H...O angles versus N...O distances are studied.